The Use of Media in English Teaching and Learning Vocabulaty at SMP Negeri 1 Luwuk - Yusniati N. Sabata; Mey Angriani Kantala (English Education Study Program, 2021)
This research aims to identify and described the application of media used by teachers at SMP Negeri 1 Luwuk in teaching. The type of this research was descriptive qualitative. This research used two instruments to obtain data, namely observation and interviews. The subjects of this research were teachers at SMP Negeri 1 Luwuk. Based on the results, the researcher found the type of media used by teachers in teaching, namely: computer or Laptop, internet, modules, pictures, power points, audio, Zoom and WhatsApp. The description of the application of the Teaching media is: based on the result of observations and interviews, the researcher draws the conclusion that the application of all media used by teachers for online learning is continuous and interconnected between one media and another so that the online learning process runs smoothly.